Spontaneous abdominal bleeding associated with SARS-CoV-2 infection: causality or coincidence? Abdominal bleeding and SARS-CoV-2 - Sposato, Bruno; Croci, Leonardo; Di Tomassi, Maurizio; Puttini, Camilla; Olivieri, Carmela; Alessandri, Mario; Ronchi, Maria Cristina; Donati, Elisa; Garcea, Alessio; Brazzi, Angelica; Migliorini, Maria Giovanna; Chigiotti, Silvia; et al. (Acta Biomedica Atenei Parmensis, 2021)
Authors present 6 cases of abdominal bleeding associated with COVID-19, representing 1.35% of all hospitalized COVID-19 patients and hypothesize that there could be, although not very frequently, a relationship between SARS-CoV2 and bleeding. They excluded a side effect of the low molecular weight heparin therapy that all patients underwent during the course of the disease or other possible causes. Alterations of the coagulation state or a weakness of the vascular wall due toa presumed endotheliitis SARS-CoV-2 infection induced, are hypothesized by the authors. Investigation and follow-up for possible hemorrhagic problems in patients with COVID-19 is recommended. In particular, clinicians should be vigilant about retroperitoneal hemorrhage in COVID-19 patients. In addition to the fact that these patients are being treated with anticoagulants, anemia and abdominal pain are the signs that should lead us to suspect this type of haemorrhage. More studies are needed to understand if COVID-19 can be directly associated with bleeding. (www.actabiomedica.it)